Awareness of cervical cancer vaccination among educated females: a Bangladeshi perspective - Taniya, Sumaiya Akter (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.